2003
DOI: 10.1007/s11325-003-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Breathing and Continuous Positive Airway Pressure (CPAP) in Patients with Obstructive Sleep Apnea (OSA)

Abstract: Although nasal continuous positive airway pressure (nCPAP) treatment is the most efficient therapy for obstructive sleep apnea (OSA), compliance with therapy is poor because of several side effects. Among these adverse effects some are related to the reactions of the nose to nCPAP which are briefly described. In a long-term survey of 109 OSA patients, 80.6% continued nCPAP for at least 3 years until the last follow-up. Follow-up ranged between 0.8 and 109 months with a mean time of 43 (SD +/- 24.7) months. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 39 publications
0
14
1
1
Order By: Relevance
“…Compliance with CPAP therapy has been reported to range from 46.6 to 86% [26][27][28][29][30], and thus, compliance with CPAP, which was not evaluated in the present study, may have affected our results. Actually, 4 of the 6 patients (66.7%) that refused CPAP developed atelectasis.…”
Section: Discussionmentioning
confidence: 78%
“…Compliance with CPAP therapy has been reported to range from 46.6 to 86% [26][27][28][29][30], and thus, compliance with CPAP, which was not evaluated in the present study, may have affected our results. Actually, 4 of the 6 patients (66.7%) that refused CPAP developed atelectasis.…”
Section: Discussionmentioning
confidence: 78%
“…However, any correlation between the PAP level and PAP compliance has not been clearly identified. Several studies on PAP therapy have not found any correlation between these two parameters (14-17). …”
Section: Discussionmentioning
confidence: 90%
“…22 In a study from UK, 77% were still using CPAP at three years and median use of CPAP those continuing therapy was 5.3 hours/night. 23 In another UK-based study of over 1000 OSA patients, 4.5% patients refused CPAP treatment (these were more often female and current smokers) and during follow-up 20% stopped treatment, primarily because of a perceived lack of benefit. Methods of survival analysis showed that 68% of patients continued treatment at 5 year.…”
Section: Rates Of Compliancementioning
confidence: 99%